Recasting Red culture in proletarian Japan : childhood, Korea, and the historical Avant-Garde - Perry, Samuel, 1969- (University of Hawaiʻi Press, 2014)
Recasting Red Culture turns a critical eye on the influential proletarian cultural movement that flourished in 1920s and 1930s Japan. This was a diverse, cosmopolitan, and highly contested moment in Japanese history when notions of political egalitarianism were being translated into cultural practices specific to the Japanese experience. Both a political and historiographical intervention, the book offers a fascinating account of the passions--and antinomies--that animated one of the most admirable intellectual and cultural movements of Japan's twentieth century, and argues that proletarian literature, cultural workers, and institutions fundamentally enrich our understanding of Japanese culture. What sustained the proletarian movement's faith in the idea that art and literature were indispensable to the task of revolution? How did the movement manage to enlist artists, teachers, and scientist into its ranks, and what sorts of contradictions arose in the merging of working-class and bourgeois cultures? Recasting Red Culture asks these and other questions as it historicizes proletarian Japan at the intersection of bourgeois aesthetics, radical politics, and a flourishing modern print culture. Drawing parallels with the experiences of European revolutionaries, the book vividly details how cultural activists "recast" forms of modern culture into practices commensurate with the goals of revolution. Weaving over a dozen translated fairytales, poems, and short stories into his narrative, Samuel Perry offers a fundamentally new approach to studying revolutionary culture. By examining the margins of the proletarian cultural movement, Perry effectively redefines its center as he closely reads and historicizes proletarian children's culture, avant-garde "wall fiction," and a literature that bears witness to Japan's fraught relationship with its Korean colony. Along the way, he shows how proletarian culture opened up new critical spaces in the intersections of class, popular culture, childhood, gender, and ethnicity